Global and unbiased detection of splice junctions from RNA-seq data - Ameur, Adam (BioMed Central, 2010)
We have developed a new strategy for de novo prediction of splice junctions in short-read RNA-seq data, suitable for detection of novel splicing events and chimeric transcripts. When tested on mouse RNA-seq data, >31,000 splice events were predicted, of which 88% bridged between two regions separated by ≤100 kb, and 74% connected two exons of the same RefSeq gene. Our method also reports genomic rearrangements such as insertions and deletions.